Use of direct near‐infrared fluorescent lymphography for thoracoscopic thoracic duct identification in 15 dogs with chylothorax. Issue 2 (6th November 2017) - Steffey, Michele A.; Mayhew, Philipp D.
Abstract: Objective: To describe and assess techniques of intraoperative near‐infrared fluorescence lymphography (NIRFL) using indocyanine green (ICG) for lymphatic duct identification during thoracoscopic thoracic duct (TD) ligation in dogs. Study design: Retrospective case series. Animals: Dogs (n = 15) with naturally occurring chylothorax that underwent TD ligation. Methods: Medical records of dogs treated with thoracoscopic TD ligation in which NIRFL was utilized for intraoperative TD identification were reviewed. Data retrieved included CT lymphography (CTL) and surgical data, fluorophore dose and injection site, and timing and quality of operative TD identification. Results: Preoperative CTL was successful in 13/15 dogs and operative NIRFL was successful in 15/15 dogs. Popliteal lymph node injection achieved successful NIRFL within ≤10 minutes in 7/11 in which it was attempted. TDs identified by NIRFL imaging correlated with TDs identified by preoperative CTL in 12/13 cases in which CTL was achieved. In 1/13 cases, NIRFL identified small lymphatics not visible on CTL. In 5/9 cases in which methylene blue (MB) and ICG were combined for operative lymphography, no ducts or fewer ducts were recorded as identifiable by visible MB than by NIRFL or CTL. The median dose of ICG to achieve NIRFL imaging was 0.05 mg/kg. Thoracoscopic TD ligation was successfully achieved in all patients. Conclusion: NIRFL is a viable technique to aid in TD identification during thoracoscopy. High contrast NIRF illumination of the TD can be achieved with successful intraparenchymal injection of ICG into the popliteal lymph node.